Mixed-phenotypic acute leukemia series from tertiary care center - Ravikiran N Pawar; Sambhunath Banerjee; Subhajit Bramha; Shekhar Krishnan; Arpita Bhattacharya; Vaskar Saha; Anupam Chakrapani; Saurabh Bhave; Mammen Chandy; Reena Nair; Mayur Parihar; Neeraj Arora; et al. (Wolters Kluwer Medknow Publications, 2017)
Introduction: Mixed-phenotype acute leukemias (MPALs) are a heterogeneous group of rare leukemias constituting approximately 2%-5% of all leukemias, in which assigning a single lineage of origin is not possible. They are diagnosed by either the presence of antigens of more than one lineage or by the presence of dual population of blasts belonging to two or more lineages. We highlight the clinicopathological, immunophenotype, and genetic data of a cohort (n = 14) of patients diagnosed and treated at our center. Materials and Methods: We retrospectively analyzed consecutive cases of MPAL diagnosed in our flow cytometry laboratory from May 2012 to August 2015. These cases were diagnosed based on immunophenotyping of peripheral blood/bone marrow aspirates and morphology/genetics wherever available as per the World Health Organization (WHO) 2008 guideline. Results: Among 628 consecutive acute leukemia (AL) cases diagnosed and evaluated during this period, we identified 14 (2.2%) patients with MPAL fulfilling WHO 2008/EGIL criteria for immunological characterizing of AL criteria. Majority of these were males (n = 8, male:female ratio 1.3:1) and adults (n = 11, 78.5%). The median age of this cohort was 41 years (range 2-80). These cases were further classified as: B/myeloid (n = 9), T/myeloid (n = 4), and B/T MPAL (n = 1). Cytogenetics was available in 12 out of 14 cases, out of which, three cases had normal karyotype, three with t(9;22)(q34;q11), and two cases with complex karyotype. We also came across a rare case of B + T lymphoid MPAL who had mixed-lineage leukemia gene t(v; 11q23) rearrangement. Conclusion: MPAL is a complex entity with heterogeneous clinical, immunophenotypic, cytogenetic, and molecular features. Multiparametric flowcytometry by using comprehensive antibody panels is a valuable tool for diagnosis. Subsequent cytogenetic and molecular analysis for further prognostic stratification and treatment modalities are important.